Implementasi Framework Bootstrap Pada Pembuatan Website Informatif dan Pendaftaran di Klinik Hewan - Permatahati, Ita; Wahyu Setiya Putra, Yusuf; Ailul Ulun, Nutfah (Jurnal Riset Sistem dan Teknologi Informasi, 2023)
This Veterinary Clinic is located in Magelang City and has been established since 2017. Pancea Veterinary Clinic has never used computerized health information media such as a website until now. So far, they only use conventional media to provide information about clinical services. Registration is then also manual in the sense that the patient (animal) must be brought directly to the clinic for registration. The manual registration process for one patient (animal) takes approximately 10 minutes. In this article, researchers analyze the ins and outs of existing problems and try to provide solutions for the system being developed to achieve maximum results. The Bootstrap framework is used to create a user-friendly website in terms of appearance and the SDLC information system development method is adopted. Perform process model design using DFD model, database design, interface design, and relationships between tables. After implementing a health information system, clinics can reduce costs and attract more patients to the clinic because they already know the advantages that exist in the clinic. Patients can then register with the online registration system without having to come to the clinic and queue.